A Theory of Signalling During Job Search, Employment Efficiency, and "Stigmatised" Jobs - McCormick, Barry (Review of Economic Studies, 1990)
This paper discusses why redundant skilled workers may be reluctant to accept interim unskilled jobs. If skilled work is more satisfying or less arduous for highly productive workers, then such workers invest more in moving quickly between skilled jobs. Thus, high productivity workers tend to search on-the-job, and if unemployed will specialise in job search, rather than take an interim position. If individual differences in productivity are known to the worker but not the potential employer, then search strategy may be used as a productivity signal, with more than the efficient proportion of workers searching on-the-job and too few accepting interim unskilled jobs. Optimal policy requires a subsidy on interim unskilled jobs.